Pengembangan Sistem Aplikasi Latihan Kebugaran pada Pemula berbasis Android - Allen Nazario Istalaksana; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
During this pandemic, almost all activities are limited from work, study, worship to physical activityoutside the home. Fitness training venues were also affected because it was feared that the virus couldbe transmitted through shared tools, causing the choice of exercising at home to be a safe way. To dosports with the right movements, basic techniques or guidelines are needed to understand the movementsand the resulting effects. An instructor can help, but there are some drawbacks such as not feelingcomfortable, the costs incurred, and so on. With the development of today's technology, an instructorcan be replaced by an application that can help beginners or ordinary people do sports movementscorrectly. The solution that the author did was to develop an application to train body fitness based onandroid. This application will be developed using the waterfall model software development method.The system will display an image of the exercise movement as well as other features that support theexercise performed by the user. Blackbox and whitebox testing produces test results that are 100% validin all test cases. Compatibility testing results in the application system being able to run on the Android8.0 operating system and above. System Usability Scale testing is obtained by testing the application tousers with the results of an average usability value of 72.5 which is included in the good usabilitycategory.